PENGEMBANGAN MODUL GEOMETRI ANALITIK BIDANG BERBASIS CONTEXTUAL TEACHING LEARNING (CTL) UNTUK MENINGKATKAN KOMPETENSI MAHASISWA UNIVERSITAS RIAU KEPULAUAN (UNRIKA) - Gusmania, Yessi; Pamungkas, Tubagus (JURNAL DIMENSI, 2015)
Pursuant to class perception of at program of study of education of mathematics of University of Riau Archipelago ( UNRIKA) that student not yet owned the source learn adequate to support the study process in class. During the time, teaching materials used  not yet effective because amount of student of many and heterogeneous in character. For a while there is no practical teaching materials from lecturer as book of student hold in the lecturing. providing product in the form of Analytic geometry module of area base on the Contextual Teaching Learning (CTL) valid , praktikalitas, and effective to increase interest of student of Program of Study of Education of Mathematics of University of Riau Archipelago ( UNRIKA).This Research procedure use the model of Instruksional Development Institute ( IDI) consisted of by 3 phase, that is phase analyse the muka-belakang  At prototype phase conducted by two phase that is phase of validasi and praktikalitas.Tahap effectiveness is assessment phase, where [at] this phase is investigated to through the activity observation and result of learning student. This research in conducting at Program of Study of Education of Mathematics of University of Riau of Archipelago of Analytic eye kuliah Geometry of Area that is semester student 3 summed uply 37 student people.Result of this research indicate that the result validasi from validator show the module base on the CTL developed at Analytic Geometry lecturing of Area is valid, Praktikalitas Module base on the CTL can generate the enthusiasm learn and creativity berfikir of because is easy to comprehended and like hence it. Efektifitas perceived at lecturing execution by using this module is activity and result of learning student. From deskripsi of result of learning semester student 3 Program of Study of Education of generation Mathematics 2014 A obtained more than 70% student get the value more than 65. This means module can be told effective.